2020
DOI: 10.47201/jamin.v2i2.53
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Gaji dan Insentif terhadap Kinerja Karyawan bagian produksi PT. Uniplastindo Interbuana Pandaan

Abstract: This study aims to describe the effect of salary and incentives on the performance of employees of PT. Unilastindo Interbuana Pandaan simultaneously, partially and most dominantly. The method used in this study is a descriptive method with a quantitative approach, data analysis techniques that are validity, reliability, multiple linear regression with F test and t test. The validity test results obtained by the calculated r value of the variable salary, incentives and employee performance is greater than the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
2
7
0
5
Order By: Relevance
“…As the opinion of Hasibuan which states that incentives are additional remuneration given to certain employees whose performance is above the standard performance [16]. The results of this study support Pasaribu and Irsutami [5], Sari et al [3], Ratnasari and Mahmud [4] who state that incentives have an effect on performance.…”
Section: Effect Of Incentives Infrastructure and Work Environment Partially On Teacher Performancesupporting
confidence: 78%
See 1 more Smart Citation
“…As the opinion of Hasibuan which states that incentives are additional remuneration given to certain employees whose performance is above the standard performance [16]. The results of this study support Pasaribu and Irsutami [5], Sari et al [3], Ratnasari and Mahmud [4] who state that incentives have an effect on performance.…”
Section: Effect Of Incentives Infrastructure and Work Environment Partially On Teacher Performancesupporting
confidence: 78%
“…Incentives are a driving factor for teachers to work better so that their performance can increase. The research results of Sari et al [3], as well as Ratnasari and Mahmud [4] found that incentives affect teacher performance. However, the results of research by Pasaribu and Irsutami found that incentives did not affect teacher performance [5].…”
Section: Introductionmentioning
confidence: 95%
“…Pendapat dari (Waloyo, 2020: 18) aspek -aspek yang mempengaruhii kinerjai karyawan antara lain hasil kerja, perilaku kerja, sifat pribadi. Indikator -indikator dalam mengukur kinerja karyawan menurut (Ratnasari & Mahmud, 2020), prestasi kerja, disiplin kerja, efektivitas dan efisiensi kerja, tanggung jawab serta hubungan antar sesama.…”
Section: Kinerja Karyawanunclassified
“…Hal ini juga sesuai dengan ulasan dari (Suryani & Kristianti, 2020) bahwa variabel insentif berpengaruh positif dan signifikan terhadap variabel kinerja karyawan. Hal ini juga sesuai dengan ulasan dari (Ratnasari & Mahmud, 2020) variabel insentif yang paling dominan berpengaruh terhadap kinerja karyawan.…”
Section: Uji Pengaruh Uji Regresi Linear Bergandaunclassified
“…Hasil peneitian dari Shinta & Siagian (2020), Sukoco dkk (2020), serta Ratnasari & Mahmud (2020) menunjukan bahwa insentif berpengaruh positif terhadap kinerja karyawan.…”
Section: Latar Belakangunclassified